9514 1404 393
Answer:
x > -5
Step-by-step explanation:
(2/5)(x -1) < (3/5)(x +1) . . . . . given
2(x -1) < 3(x +1) . . . . . . . . . . .multiply by 5
2x -2 < 3x +3 . . . . . . . . . . . eliminate parentheses
-5 < x . . . . . . . . . . . . . . . . . . add -2x-3 to both sides
This matches the second answer choice: x > -5.
Answer:
I think this is the answer.
Step-by-step explanation:
I think it is C. but I am unsure, because I think it might also be able to be B.. Uh! I am so confused, but C. is my best guess.
This looks complicated
lets simplify both sides
By multiplying top and bottom by the conjugate:-
left side = (5-3i)(x + iy) (4+5i) (5-3i)(x + iy) (4+5i)
------------------------ = ------------------------
(4-5i)(4+5i) 41
right side = (2 + i + 3-4)(2+i - 3 + 4i) (by Difference of 2 squares)
= 5-3i)(-1 + 4i)
so as left side = right side
(5-3i)(x+yi)(4+5i) = 41 (5-3i)(-1+5i)
5-3i is common so:-
(x + iy)(4+5i) = 41(-1+5i)
4x +5xi + 4yi - 5y = -41 + 205i
4x - 5y + (5x + 4y)i = -41 + 205i
EQuating coefficients we are left with the system of equations
4x - 5y = -41
5x + 4y = 205
solving this gives x = 21 and y = 25